CEP55 Inhibitor: Extensive Computational Approach Defining a New Target of Cell Cycle Machinery Agent - Beni Lestari; Rohmad Yudi Utomo (Tabriz University of Medical Sciences, 2022)
Purpose: Centrosomal protein 55 (CEP55) is a pivotal protein for cytokinesis during cell division. This study aimed to provide a comprehensive information about the CEP55 gene, including its expression pattern in several cancer types, conduct functional domain analysis across species, and perform a computational approach for potential inhibitors of CEP55. Methods: The expression levels of CEP55 in different cancers were analyzed using the Oncomine and TCGA databases. Evolutionary analysis of the CEP55 gene in various species was performed using MEGA-X software. Molecular docking analysis was used to screen the binding affinity of several natural products on CEP55-ALIX binding interaction. Results: High CEP55 expression was observed in 16 datasets of different cancer types. The high expression of the CEP55 protein was associated with worse outcomes in cancer treatments. Phylogenetic and evolutionary analyses revealed that the amino acid residues essential for CEP55 binding and localization were mostly conserved across vertebrates. Seventeen plant-based compounds were docked against the CEP55 protein to determine their binding affinities and illustrated specific sites of interaction for predicting novel protein-drug interactions. Flavanol compounds epigallocatechin gallate and catechin possessed superior binding affinity to all other compounds owing to the substitution of gallic ester or hydroxyl groups on the C3 position. Conclusion: This study provides comprehensive information about the CEP55 gene and insights for designing potent inhibitors against CEP55 signaling.